STRATEGI PENGEMBANGAN OBJEK WISATA KAWAH PUTIH TINGGI RAJA KECAMATAN SILAU KAHEAN KABUPATEN SIMALUNGUN SUMATERA UTARA - Liza Fadila Habib; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Simalungun has a lot of potential with a variety of attractions such as the natural and cultural attractions are quite interesting that can be relied upon to be developed as a tourist attraction, one of which is the attraction White Crater High King of the District Glare Kahean Simalungun North Sumatra. Potential attractions and characters in Simalungun supported by government policy Simalungun listed in the Vision and Mission District Simelungun in Regional Economic Development. White crater nature reserve is located in the village of High King, District Glare Kahean, Simelungun District, North Sumatra. The crater is located in District Glare Kahean appeared and were among the limestone hill has its own exotic. In contrast to the Kawah Putih in Bandung, White Crater High King surrounded by pandanus forest is very high, blue water with chunks of sulfur that occur naturally such as a thick layer of ice. In this place there are also original hot springs which form the limestone hills of sulfur hardened. High King attractions include the nature reserve with an area of approximately 167 ha. Distance from city Pematangsiantar approximately 121 Km Bedagai Serdang regency. The number of tourists coming too big impact for the district, in addition to adding the PAD also can reduce the unemployment rate. To achieve this course of action that governments must do attraction development strategies.The concept of the theory used in this research is the development strategy, SWOT analysis. The method used in this study is a qualitative method using descriptive approach. Data collection techniques using interview techniques and documentation.These results indicate that the development strategy conducted by the District Government Simelungun not maximized. This is evident from the unavailability of infrastructure and adequate infrastructure kuranag.Keywords: Strategy, Development, Attractions